2015
DOI: 10.1109/jlt.2015.2397276
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Short-Term Polarization Noise and Related Spectral Decoherence in All-Normal Dispersion Fiber Supercontinuum Generation

Abstract: The supercontinuum generated exclusively in the normal dispersion regime of a nonlinear fiber is widely believed to possess low optical noise and high spectral coherence. The recent development of flattened all-normal dispersion fibers has been motivated by this belief to construct a general-purpose broadband coherent optical source. Somewhat surprisingly, we identify a large short-term polarization noise in this type of supercontinuum generation that has been masked by the total-intensity measurement in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Hence, it qualifies as an avoidable technical noise source and does not represent a fundamental noise limitation of ANDi SC generation. As PM fiber is the preferred solution for the targeted applications and the experimentally measured SC spectra correspond very well to numerical simulations assuming pulse propagation in a single polarization axis [30,32], this is also the approach we use in this manuscript.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Hence, it qualifies as an avoidable technical noise source and does not represent a fundamental noise limitation of ANDi SC generation. As PM fiber is the preferred solution for the targeted applications and the experimentally measured SC spectra correspond very well to numerical simulations assuming pulse propagation in a single polarization axis [30,32], this is also the approach we use in this manuscript.…”
Section: Introductionmentioning
confidence: 66%
“…(5), but would not experience additional nonlinear noise amplification as it is the case for anomalous dispersion pumping [46]. Indeed, experimental relative intensity noise (RIN) measurements have demonstrated that the noise characteristics of ANDi SC generated in the coherent regime are essentially identical to the RIN of the pump laser [24,32].…”
Section: Pump Sources With Noise Levels Exceeding the Shot Noise Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1041-nm 220-fs 80-MHz pulses from a Yb:KYW laser (femtoTRAIN IC model-Z, High Q Laser) were coupled by an aspheric lens (C330TME-C, Thorlabs) into a 21-cm custom-made photonic crystal fiber (NL-1050-NEG-PM-FUD, NKT Photonics) along the slow-axis of the fiber 36 . The linear birefringence of the fiber was estimated to be 4.2×10 −4 by spectral interferometry, ensuring small (<0.5%) nonlinear depolarization along the fast axis of the 21-cm fiber.…”
Section: Methodsmentioning
confidence: 99%
“…Another important issue is the polarization state of different spectral components contained in the broad supercontinuum spectrum. Such changes in the polarization state are the source of hidden intrinsic noise [22]. The differences in the Polarization Extinction Ratio (PER) between orthogonal polarizations for PM (LMA-PM-5) and non-PM (NL-NEG-1050-1) fibers during pulse energy changes are presented in Fig.…”
mentioning
confidence: 99%